Possibilities of adaptation of milk-processing plants to new economic conditions by means of their introduction into infrasystems - Bielinska, N. S. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The paper considers the problems dealing with new organization of integrated control of material flow, starting with the supply of resources for the plant to consumer. The influence of infrastructure activity on the formation of increased use value which is increased due to the second trend, connected with the process of globalization is considered, as a result of research, the condusion is made that at present stage of development more and more companies become open companies that is why direct systems turn out into infrasystems, connected with the information age.